Impact of Accounting Information Systems (AIS) On Internal Auditors: A Comparative Study between Bangladesh and Turkey - Maruful Islam, (International Journal of Scientific Research and Management (IJSRM), 2023)
Technological improvements have led to a widespread use of accounting information systems (AIS) in companies and industries across the globe. Moreover, AIS offers thorough and trustworthy information to both internal and external users by typically focusing on six main areas: people, procedures, data, software, IT infrastructure, and internal controls. The aim of this study is to determine how AIS have affected internal auditors in Bangladesh and how those effects compare to or diverge from those found in a related and unique study carried out in Turkey. Both primary and secondary sources were used to gather the data. Using close-ended self-administered questionnaires I analyzed the impact of accounting information systems on internal auditors in Bangladesh and using cross-country analysis measured these results against a similar study conducted in Turkey. In this work, SPSS is employed for validation. I posed 12 questions in the questionnaire, and 60 internal auditors from multiple sectors and various regions of Bangladesh responded. The results strongly indicate that internal auditors in Bangladesh believe that AIS contributes positively to their work, and the conclusions are remarkably similar to those of the prior study conducted in Turkey. This study definitively answers the question regarding the positive impact of AIS on internal auditors in Bangladesh and having similarities with Turkey. This study is relevant to a wide range of professions, not only internal auditors, because it emphasizes the relevance of information technology in the corporate world.